2020
DOI: 10.1155/2020/5248365
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Interaction of Thyroid-Kidney Organs in Disease States

Abstract: Purpose. Thyroid hormones play an important role in growth, development, and physiology of the kidney. The kidney plays a key role in the metabolism, degradation, and excretion of thyroid hormones and its metabolites. The aim of this study is to investigate the prevalence of disease states of thyroid-kidney organs and detecting the correlation between thyroid and kidney function abnormalities. Materials and Methods. In this retrospective study, a total of forty-five patients with thyroid and kidney dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…In our survey hypothyroidism was related to the duration of dialysis as mentioned by other authors (15). Amiri reported 66.6% of primary hypothyroidism who are having chronic kidney disease and 2.2% of subclinical hypothyroidism (19). Hypothyroidism is common in chronic kidney disease patients with or without dialysis.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In our survey hypothyroidism was related to the duration of dialysis as mentioned by other authors (15). Amiri reported 66.6% of primary hypothyroidism who are having chronic kidney disease and 2.2% of subclinical hypothyroidism (19). Hypothyroidism is common in chronic kidney disease patients with or without dialysis.…”
Section: Discussionsupporting
confidence: 68%
“…Aryee et al in Ghana found the same rate of hyperthyroidism in chronic kidney disease patients (2%) (14). In other cases, 15.5% of primary hyperthyroidism and 6.6 subclinical hyperthyroidism were noted (19).…”
Section: Discussionmentioning
confidence: 86%
“…Thus, help in delay in the need for renal replacement. 24,25 The CKD mediated thyroid function abnormalities can be recovered after renal transplantation. A thyroid profile with abnormalities is caused by CKD can be reversed by kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%